Transcatheter aortic valve implantation (from inception to standard treatment): a single-center observational study - Høydahl, Martin Petter; Busund, Rolf; Rösner, Assami; Kjønås, Didrik (Frontiers in Cardiovascular Medicine, 2024)
Background Treatment of severe aortic stenosis with transcatheter aortic valve implantation (TAVI) was introduced in 2002. Since then, TAVI has become the primary treatment approach worldwide for advanced-age patients and younger patients with severe comorbidities. We aimed to evaluate the changes in patient demographics, complications, and mortality rates within 13 years. Methods This retrospective observational study included 867 patients who underwent TAVI at the University Hospital of North Norway in Tromsø from 2008 to 2021. The 13-year period was divided into period 1 (2008–2012), period 2 (2013–2017), and period 3 (2018–2021). The primary objective was to evaluate the changes in periprocedural (30 days), early (30–365 days), and late mortality rates (>365 days) between the periods. The secondary objective was to evaluate late mortality rates by sex and age groups: <70 years, 70–79 years, 80–89 years, and ≥90 years. Results The periprocedural mortality rates for periods 1, 2, and 3 were 10.3%, 2.9%, and 1.2%, respectively (P < 0.001). The early mortality rates were 5.6%, 5.8%, and 6.5%, respectively. No significant differences were observed in late mortality by sex or age group (<70, 70–79, and 80–89 years) with a median survival of 5.3–5.6 years. The median survival in patients aged ≥90 years was 4.0 years (P = 0.018). Conclusion Our findings indicate that most patients are octogenarians, and the burden of their comorbidities should be highly considered compared to their age when evaluating the procedural outcomes. As the incidence of most complications related to TAVI has decreased, the rates of permanent pacemaker implantation remain high. Important advancements in diagnostics, valve technology, and procedural techniques have improved the periprocedural mortality rates; however, early mortality remains unchanged and poses a clinical challenge that needs to be addressed in the future.